2010
DOI: 10.1016/j.jvs.2010.03.043
|View full text |Cite
|
Sign up to set email alerts
|

Stent Graft versus Balloon Angioplasty for Failing Dialysis-Access Grafts

Abstract: with TEVAR was impressive. With longer follow-up, this may translate into improved survival with fewer long-term complications. Stent Graft versus Balloon Angioplasty for Failing Dialysis-Access GraftsHaskal ZJ, Trerotola S, Dolmatch B, et al. N Engl J Med 2010;362:494-503. Conclusion: Revision of a venous anastomotic stenosis of a prosthetic dialysis access graft with a stent graft provides longer-term patency and freedom from repeat intervention than revision with standard balloon angioplasty.Summary: Sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
192
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(195 citation statements)
references
References 0 publications
1
192
1
1
Order By: Relevance
“…In the case of repeat stent occlusion, it is necessary to surgically place the graft again. A number of current studies describe improved patency rates compared to PTA alone for stenoses of the dialysis graft in the region of the venous anastomosis and the venous outflow when using covered stent grafts [79,80]. The study by Haskal et al is a prospective randomized multicenter study with only a six-month follow-up [80].…”
Section: Insufficient Dialysis Graftmentioning
confidence: 99%
“…In the case of repeat stent occlusion, it is necessary to surgically place the graft again. A number of current studies describe improved patency rates compared to PTA alone for stenoses of the dialysis graft in the region of the venous anastomosis and the venous outflow when using covered stent grafts [79,80]. The study by Haskal et al is a prospective randomized multicenter study with only a six-month follow-up [80].…”
Section: Insufficient Dialysis Graftmentioning
confidence: 99%
“…A previous 6-month trial comparison between stent grafts and PTA alone also reported better patency rates with the stent grafts (47). However, in the 6-month report, the graft thrombosis rates were not significantly different than the rates after PTA alone, and graft survival rates were not reported.…”
Section: Endovascular Approachesmentioning
confidence: 75%
“…P atent vascular access is critical for patients with kidney failure who rely on regularly scheduled hemodialysis. Detailed evidence-supported guidelines have been developed regarding vascular access placement (1)(2)(3)(4), and much has been written about the surveillance, maintenance, biology, cost, and interventional techniques for these accesses (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). Similarly, predictors of success following radiological intervention of these access sites have been evaluated, including pressure, the degree of stenosis, and procedure type (16,17).…”
Section: Resultsmentioning
confidence: 99%
“…Percutaneous endovascular techniques have proven to be successful with the added benefits of lower cost and periprocedural morbidity when compared to surgical thrombectomy (3,11). Studies have shown that surveillance of indwelling arteriovenous (AV) grafts can reduce the number of thromboses, and that procedure technique can influence success (11,12,(22)(23)(24). Allon et al (23) reported dramatic improvement in the maintenance of AV grafts in their dialysis population on implementation of a multidisciplinary approach that involved the transition of procedures to an outpatient setting, aggressive surveillance, and detailed logistical support.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation